Assessing iron age marsh-forts : with reference to the stratigraphy and palaeoenvironment surrounding the Berth, North Shropshire - Norton, Shelagh, (Archaeopress Archaeology, 2021)
This volume assesses marsh-forts as a separate phenomenon within Iron Age society through an understanding of their landscape context and palaeoenvironmental development. These substantial monuments appear to have been deliberately constructed to control areas of marginal wetland and may have played an important role in the ritual landscape.